(untitled) (Philological Studies, 2019)
Macedonian language status presented in this paper is upon it usage as native language, teaching language, official language and foreign language. This paper is prepared with the intention of discussing actual situation and possibilities for future development in all mentioned statuses of Macedonian language utilized in R. Macedonia and abroad: in neighbouring countries, European countries and overseas countries.